DIGITAL TRANSFORMATION IN CAREER GUIDANCE SERVICES: A SYSTEMATIC LITERATURE REVIEW - Sudjani; Wawan Eko Putra (LPPM Universitas Negeri Jakarta, 2025)
Digital transformation in career guidance services is becoming increasingly important along with dynamic changes in the work landscape, digitalisation of industries, and more complex career readiness demands in the digital era. Despite the increasing use of technology in career guidance, there is still a gap in the systematic understanding of effective digital transformation models and how the role of career counsellors changes in the digital context. This Systematic Literature Review (SLR) used the PRISMA methodology to analyse the current literature on digital transformation in career guidance. A systematic search was conducted on the Scopus database with predefined keywords, resulting in 67 records which were then filtered into 7 high-quality articles published between 2019-2025. Findings show that digital transformation significantly improves the effectiveness of career guidance services through increased accessibility, personalisation of AI-based services, and the use of digital platforms. Four main models were identified: Cloud-based Career and Educational Guidance System (CEGS), integrated digital platforms, hybrid systems, and AI/machine learning-based systems. The role of career counsellors evolved from traditional information providers to digital facilitators requiring technological competence.